Financial Report Quality through Accounting Information System Implementation: Kualitas Laporan Keuangan Melalui Implementasi Sistem Informasi Akuntansi - Hayuningtyas, Widya Retno; Rahmawati , Imelda Dian (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Public sector financial reporting requires reliable systems to enhance transparency and accountability. Specific Background: Regional governments continue to face issues such as errors, overpayments, and weak compliance that indicate insufficient report quality. Knowledge Gap: Prior studies show inconsistent findings regarding the roles of accounting information systems (AIS) and human resource quality in improving report quality. Aims: This study aims to analyze the contribution of AIS implementation and human resource quality to the financial report quality in a local government office. Results: The findings indicate that AIS implementation contributes significantly to improving report quality, while human resource quality strengthens the relationship between AIS and reporting outcomes. Novelty: This study integrates signaling theory and contextual issues from the selected region to provide a more comprehensive understanding of reporting practices. Implications: The results highlight the importance of strengthening AIS utilization and enhancing staff competency to support transparent and accountable public financial management. Highlights : Examines AIS implementation within local government context. Identifies HR quality as a moderating factor. Provides evidence aligned with signaling theory. Keywords:Accounting Information System, Financial Reporting, Human Resources, Public Sector, Moderation